Only Moments - Joshua Cupps (Stimulus: A Medical Humanities Journal, 2023)
"Only Moments" was inspired by a feeling to express my grief and better understand my emotions surrounding it. Writing has allowed me to cope with and physically interact with difficult life events, thoughts, and ideas, so it felt natural as a medium to create this piece. The last few years have been full of both great happiness and great sorrow, particularly from the loss of loved ones. I wrote this piece about my grandfather’s passing, whom I was very close to. I felt that grieving my grandfather was difficult because he died of cancer, resulting in a slow deterioration of his body. I wanted to capture the confusing mixture of feelings I had grieving for someone who was still here but gradually losing them over the span of only a few days. Namely, I wanted to capture the experience of remembering the precious moments we shared as well as moments that I regretted, wondering if he could ever hear my apologies or if he could hear me at all. I wanted to write about the pain and regret of how I spent some of those moments and wishing I could only have a moment longer with him.